Study of vehicle movements in mixed traffic flow at junctions - Nadia Raihanah Haron Narasip (2014)
The capacity at a junction is affected by the proportion of Heavy-Goods-Vehicles (HGVs). The understanding of the behaviour of HGVs at junctions is critical in estimating the efficiency of a junction in terms of the junction capacity. HGVs impose a significant effect on traffic flow at junctions due to their large size. HGVs constitute the second largest vehicle population on Singapore roads. Statistics in 2013 released by the Land Transport Authority (LTA) recorded an increase in goods-vehicles from a population of 159,768 in 2011 to that of 160,417 in 2012. In this study, the efficiency of a junction is determined by analysing its capacity and safety. Capacity is analysed with the aid of parameters such as average travel times and queue lengths while safety is analysed by identifying the conflict areas at a junction and how regular the conflict arises. PTV VISSIM is utilised in the later part of the project to create simulations which are instrumental to obtain data on the relevant parameters in determining the efficiency of a junction. However, before simulations can be conducted, the data extracted from the videos taken at these junctions selected for study are analysed. Software packages such as Microsoft Excel and Avidemux are used to organise and collate data and to note the instances when the traffic signals change phases, respectively. These procedures are implemented so that simulations of these junctions can be replicated to model the usage of the junction in reality. The analysis of the results from PTV VISSIM will follow. The results obtained from PTV VISSIM include the average vehicle travel times, queue lengths and trajectory motion of the vehicles. The variables aforementioned determine how each vehicle types, mainly cars and HGVs, are affected by increase in HGV volume. In addition, Surrogate Safety Assessment Model (SSAM) is also utilised in the project to determine the frequency and type of collisions at the junctions as well as the average time to collision between vehicles. The results obtained from both PTV VISSIM and SSAM will indicate how increasing HGV volume affects different junction types in terms of their efficiency. After which, comparisons will be made with conventional methods which are based on equations, such as the Webster method and HCM, to identify the pros and cons of using PTV VISSIM to determine junction efficiency.